Waqf for Higher Education in Malaysia: Overview on Challenges - Mujani, Wan Kamal; Yaakub, Noor Inayah (European Journal of Multidisciplinary Studies, 2021)
In Malaysian higher learning institutions of public or private universities, the generation of income through endowments are recently highly recommended for financial or self-sustainability. Public universities especially, as a non-profit organisation strong endowments reflect the capacity to obtain revenues through grants or otherwise in response to a demand, in order to sustain productive processes projects at a steady or growing rate which eventually produce results and thus accomplish the mission, goals, or objectives and to obtain a surplus. However, the implementation of waqf in universities in Malaysia is not easy. Unlike endowments or other forms of income generation tools for universities, waqf is very unique and subject not only to legal restrictions but also religious principles that must be fulfilled. The paper finds that universities in Malaysia need to bear in mind the challenges of to avoid difficulties in implementing waqf.